Resveratrol derivative excited postsynaptic potentiation specifically via PKCβ-NMDA receptor mediation. (February 2020) - Tong, Jia; Gao, Jingjing; Liu, Qingzhen; He, Chenyang; Zhao, Xing; Qi, Yawei; Yuan, Tiangang; Li, Pengyan; Niu, Ming; Wang, Dongyao; Zhang, Le; Li, Weiyong; et al.
Graphical abstract: Abstract: Several decades have passed since resveratrol (RSV) was first identified in red wine. Researchers have reported the pleiotropic anti-oxidant, anti-inflammatory, anti-cancer, anti-aging, and neuronal protective effects of resveratrol and its glycosylated derivative. However, few studies have distinguished the minute differences in the properties between resveratrol and its glycosylated derivative in terms of synaptic plasticity. As an abundant natural product of glycosylated resveratrol, the derivative 2, 3, 4', 5-tetrahydroxystilbene-2-O-β-d-glucoside (TSG) has been determined to be a better option for long-term potentiation (LTP) in the hippocampus under physiological and pathological conditions than resveratrol. TSG, as well as its parent molecule RSV, could elicit early-LTP and recover fast excitatory postsynaptic potentials (EPSPs) in the hippocampus. Using various modalities, including pre- and post-whole-cell patch clamping techniques in the calyx of Held, pharmacological inhibition of the N-methyl-d-aspartic acid receptor (NMDAr) and the α-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid receptor (AMPAr) as well as protein kinase C (PKC) activation, we demonstrated that TSG, unlike RSV, could merely promote NMDA-mediated EPSC via PKCβ cascade. Our results provide new knowledge that glycosylation of resveratrol could significantly improve its specificity in promoting sole NMDAr mediation of EPSPs, in addition to improving solubility and resistance against oxidation in vivo . These observations could contribute to further exploration of pharmaceutical evaluation of glycosylated stilbene in the future.